2019
DOI: 10.1093/ije/dyz044
|View full text |Cite
|
Sign up to set email alerts
|

Are cannabis users less likely to gain weight? Results from a national 3-year prospective study

Abstract: Background Pre-clinical studies indicate increased food intake and weight gain as cannabinoid effects. Cross-sectional epidemiological studies, however, indicate lower prevalence of obesity among cannabis users. Here, we aim to study the weight-gain research question in the prospectively conducted National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). Methods NESARC was designed to produce nationally repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…Combined examination of two large epidemiological studies (NESARC and NCS-R) concluded that chronic cannabis users had significantly decreased adjusted prevalence rates of obesity, from 22%–25% in non-users to 14%–17% in users [148]. A very recent prospective analysis of NESARC data supports the above, finding that cannabis use is inversely associated with BMI increases over 3 years [149]. Several large studies have also shown inverse associations between cannabis and diabetes [150,151,152], which were corroborated by a Swedish study involving 18,000 participants, though the observed protective effects on diabetes were attenuated when adjusted for age [153].…”
Section: Cannabis Use and Metabolic Healthmentioning
confidence: 98%
“…Combined examination of two large epidemiological studies (NESARC and NCS-R) concluded that chronic cannabis users had significantly decreased adjusted prevalence rates of obesity, from 22%–25% in non-users to 14%–17% in users [148]. A very recent prospective analysis of NESARC data supports the above, finding that cannabis use is inversely associated with BMI increases over 3 years [149]. Several large studies have also shown inverse associations between cannabis and diabetes [150,151,152], which were corroborated by a Swedish study involving 18,000 participants, though the observed protective effects on diabetes were attenuated when adjusted for age [153].…”
Section: Cannabis Use and Metabolic Healthmentioning
confidence: 98%
“…The most common acute symptoms include dizziness, drowsiness, anxiety and euphoria. While preclinical studies have provided mixed findings on whether treatment with THC can result in weight gain in animals (Cluny et al, 2015;Assa-Glazer et al, 2020), the most comprehensive epidemiological study to date in humans indicated that cannabis users were less likely to gain weight than individuals who have never used cannabis (Alshaarawy and Anthony, 2019), and so this should not be considered a common side-effect of cannabis for most users, despite the common perception of cannabis use causing the "munchies" (Sansone and Sansone, 2014). These side-effects are mitigated when patients start with lower doses and wait an appropriate amount of time before increasing their dose (i.e., "start low and go slow").…”
Section: Initiating a Medical Cannabis Adjunct Trialmentioning
confidence: 99%
“…The reported anti-inflammatory effects of cannabis were greatly attenuated when body weight is controlled for. This suggests that the inverse cannabis-body weight association might explain the lower levels of circulating inflammatory biomarkers in adult cannabis users (Penner et al, 2013;Le Strat and Le Foll, 2011;Alshaarawy and Anthony, 2019), given the strong association of inflammation and adiposity (Esser et al, 2014). The results of the current study indicate elevated WBC count among heavy cannabis users, and persisted after adjusting for BMI.…”
Section: Discussionmentioning
confidence: 49%